PEMAHAMAN KONSEP MATEMATIKA SISWA DALAM MENYELESAIKAN MASALAH BANGUN DATAR - Fatqurhohman Fatqurhohman (Universitas PGRI Madiun, 2016)
This research is meant to describe the students’ understanding of Mathematics Concept related to non-routine problem in contour Shapes. This research is a qualitative research. The subject of this research are 25 students of fourth (VI) grade of SDN Mojorejo 02 Kota Batu. The data are collected through students’ response on a test given. Based on the result of this research shows that students are still unable to use Mathematics concept well in solving some problems (still tent to be procedural), students are still unable to compare by presenting alternative solution aside from response obtained, students’ mastery and understanding concept of Mathematics in solving non-routine questions are still low. Teachers are hoped to be able to provide non-routine questions in order to allow students to be accustomed with and develop ability in relation to problem solving